(untitled) (Encuentros, 2022)
This article is built from the objective of: situating the sociocultural reality based on the experiences of road cyclists in the Departmento of Nariño, Colombia. This was a qualitative investigation, with a historical-hermeneutical approach and its method was phenomenological. The results presented here arise from the application of a semi-structured interview and show that amateur, elite and professional cyclists build similar experiences. Following the ideas of the Embodiment proposed by Holmqvist, Frisén, Luanne and Pira, it is concluded that these experiences emerge from the relationship between body - instrument - cognition. This research was funded by the CESMAG University (San Juan de Pasto) and the University of Concepción (Concepción).